Studying dynamic changes in body mass and mass of internal organs in laboratory rats experimentally infected with bovine leukosis virus - E. S. Krasnikova; R. V. Radionov; A. V. Krasnikov; A. Yu. Svetozarova (Ветеринария сегодня)
Enzootic bovine leukosis has been an urgent problem of veterinary medicine both in the Russian Federation and abroad for more than a hundred years. A number of aspects have been studied quite deeply; however, there are still areas that require additional research. These include the development of a fully adequate laboratory model for reproducing bovine leukosis virus (BLV) infection. Preliminary studies have established that BLV infection of laboratory rats is accompanied by clinical, morphological and biochemical changes in the blood, signs of immune suppression, impaired immunological reactivity of the body, and morphofunctional changes in the immunocompetent cells that correlate with bovine leukosis. In this regard, it is of interest to analyze disorders caused by these dysfunctions; the disorders are demonstrated by changed morphometric characteristics of both the body and individual organs. The aim of the research was to study dynamic changes in body mass and mass of internal organs in laboratory rats experimentally infected with BLV. There was a clear body mass increase in BLV-infected laboratory rats, then followed by a decrease down to negative numbers. The reverse trend was observed for such internal organs of the experimental animals as liver, spleen, kidneys and lungs. At first, their relative mass decreased to some extent, then increased with different dynamics in groups. The heart was the exception, as its relative mass decreased and did not increase until the end of the experiment. The data obtained correlate with those provided by a number of authors that the relative mass of various organs changes in the BLV infected animals because of proliferative, inflammatory, dystrophic and atrophic processes.